FARMER’S MOTIVATION IN MAKING COMPOST FROM GOAT LIVESTOCK WASTE IN SUKA VILLAGE TIGAPANAH SUBDISTRICT KARO REGENCY NORTH SUMATRA PROVINCE - A. G, Ginting; Inggriati, N. W. T.; Suarta, G. (Jurnal Peternakan Tropika, 2022)
This research aims to determine the motivation of farmers in making compost from goat waste and the factors related to the motivation of farmers in making compost from goat waste. The research was conducted in Suka Village, Tigapanah Subdistrict, Karo Regency, North Sumatra Province from August to September 2021. The research location was determined by purposive sampling method, 45 respondents were determined by the method stratified random sampling. The analysis used is descriptive qualitative analysis and Spearman’s Level Correlation Test. The results showed that the motivation of farmers in making compost from goat waste was in the medium category. The factors that were significantly related (P<0.10) with the motivation of farmers were: formal education, non-formal education, communication intensity, knowledge, attitudes, and skills; while the factors of age, family responsibilities, livestock ownership, land tenure, and livestock experience had no significant relationship (P>0.10) with farmer motivation. Conclusion: 1) Farmers in Suka Village are moderately enthusiastic about using sheep dung to make compost. 2) Factors such as formal education, non-formal education, intensity of communication, knowledge, attitudes, and skills had significant influence on farmer’s motivation. Suggestion: to the relevant agencies to further improve guidance and counseling for goat breeders in Suka Village, in order to increase the motivation of farmers in making compost from goat waste. Keywords : Knowledge,  factors, counseling